2020
DOI: 10.1016/j.csbj.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Potential clinical drugs as covalent inhibitors of the priming proteases of the spike protein of SARS-CoV-2

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The three-dimensional structure coordinates of all the targets were retrieved from Protein Data Bank (PDB) except TMPRSS2. The homology model of TMPRSS2 was downloaded from the SARS-CoV-2 repository of SWISS-MODEL [ 36 ]. The structure was built using serine protease hepsin as a template and showed Q Mean score is -1.62 for the modeled structure.…”
Section: Methodsmentioning
confidence: 99%
“…The three-dimensional structure coordinates of all the targets were retrieved from Protein Data Bank (PDB) except TMPRSS2. The homology model of TMPRSS2 was downloaded from the SARS-CoV-2 repository of SWISS-MODEL [ 36 ]. The structure was built using serine protease hepsin as a template and showed Q Mean score is -1.62 for the modeled structure.…”
Section: Methodsmentioning
confidence: 99%
“…ii) Targeting host proteins provides another way to fight SARS-CoV-2. Li et al developed covalent inhibitors using the SCAR tool for TMPRSS2 (see introduction) and CatB/L, which prime the S protein together with TMPRSS2 [73] .…”
Section: Structure-based Computational Techniquesmentioning
confidence: 99%
“…The study identified five potential inhibitors of CatB that are neratinib, [Z]-dacomitinib, trapoxin B, HKI-357, and domatinostat and four TMPRSS2 potential inhibitors including [S]-boceprevir, [R]-boceprevir, aceneuramic acid, and lodoxamide. Moreover, trapoxin B (Kijima et al 1993 ), HKI-357 (Tsou et al 2005 ), neratinib (Tsou et al 2005 ), [Z]-dacomitinib (Garuti et al 2011 ) and boceprevir (Nazario de Moraes et al 2019 ) have already proven to be covalent inhibitors (Li and Wang 2020 ). Some other potential spike protein inhibitors (Table 1 ) are given in details as follows:…”
Section: Potential Covalent Spike Protein Inhibitorsmentioning
confidence: 99%
“…Dacomitinib, as a potent EGFR TKI irreversibly binds to the receptors and exhibits a strong cellular potency against EGFR oncogenic variants (Deeks and Keating 2018 ). In silico screening of dacomitinib in addition to neratinib and domatinostat as a cathepsin-binding drug that targets viral and host, proteins have also been reported (Li et al 2020 ).…”
Section: Potential Covalent Spike Protein Inhibitorsmentioning
confidence: 99%